PENINGKATAN PRESTASI BELAJAR EFEKTIF DAN EFISIEN MELALUI BIMBINGAN PRIBADI DAN SOSIAL PADA SISWA KELAS XI IPS 1 SMA NEGERI 1 KAYUAGUNG - Ina Ismail (LPPM STKIP PGRI Sidoarjo, 2019)
The purpose of this Classroom Action Research (CAR) is to overcome that personal and social guidance can improve student learning achievement. And to find out how to provide group services in order to increase student learning achievement. The location in question covers aspects of the place is the location where the learning process takes place namely class XI IPS 1 SMA Negeri 1 Kayuagung. The actor's aspect is the researcher, as a teacher and student of class XI IPS 1 who is involved in learning interactions. The activity aspect is group service for Improvement of Learning Achievement Through Personal and Social Guidance Fields Effective and Efficient Learning Materials with group services in class XI IPS 1 Kayuagung 1 Public High School 2017/2018 Academic Year. On effective and efficient learning material. Based on the results of the study and the learning outcomes, it can be concluded that the personal and social learning can increase the Learning Achievement of the Guidance Field in Effective and Efficient Learning Materials of the XI IPS 1 students at Kayuagung 1 Public Senior High School 2017/2018 in the first cycle of 77.54. % and second cycle 86.11%.